2012
DOI: 10.1094/pdis-11-11-0943-re
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Structure of Pseudoperonospora cubensis Populations

Abstract: Pseudoperonospora cubensis is a destructive foliar pathogen of economically important cucurbitaceous crops in the United States and worldwide. In this study, we investigated the genetic structure of 465 P. cubensis isolates from three continents, 13 countries, 19 states of the United States, and five host species using five nuclear and two mitochondrial loci. Bayesian clustering resolved six genetic clusters and suggested some population structure by geographic origin and host, because some clusters occurred m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 45 publications
6
45
0
Order By: Relevance
“…'M R-1' was among the most resistant melon cultivars in this study and in a study in South Carolina (11). Differences found in this study in disease response among melon cultigens in Michigan compared with South Carolina could be due to differences in pathogen populations or environmental conditions (21). Our data suggest that there are differences in virulence and patho genicity between Michigan and South Carolina, consistent with hy potheses that these populations are not from the southern United States.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…'M R-1' was among the most resistant melon cultivars in this study and in a study in South Carolina (11). Differences found in this study in disease response among melon cultigens in Michigan compared with South Carolina could be due to differences in pathogen populations or environmental conditions (21). Our data suggest that there are differences in virulence and patho genicity between Michigan and South Carolina, consistent with hy potheses that these populations are not from the southern United States.…”
Section: Resultssupporting
confidence: 68%
“…A previous study found similarities in the genetic cluster composition year to year (2007 to 2009) of P. cubensis populations in the United States and in Michigan, which supports these results (21). It has been proposed that Michigan downy mildew primary pop ulations originate either from the Georgia, South Carolina, and North Carolina areas or from greenhouses located along the border with Canada (18,21).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…cubensis, several isolates have been identified, and recent data suggests that the pathogen is continually evolving; this is evidenced by different genotypes of Ps. cubensis observed in various geographic regions of the United States (Lebeda and Widrlechner 2003;Quesada-Ocampo et al 2012). At present, the host range for Ps.…”
Section: Host Range and Economic Value Of Ps Cubensismentioning
confidence: 99%